Redescription of Parambassis macrolepis (Bleeker, 1856), a senior synonym of Parambassis piratica (Roberts, 1989), with descriptions of three new species of Parambassis (Ovalentaria: Ambassidae) from Sumatra and Borneo - Ghazali, Siti Zafirah; Lavoué, Sébastien; Sukmono, Tedjo; Wibowo, Kunto; Hubert, Nicolas; Mohd Nor, Siti Azizah (John Wiley and Sons, 2026)
Parambassis macrolepis (Bleeker, 1856), a poorly characterized species of glass perchlet (Ovalentaria, Ambassidae), is redescribed and Parambassis piratica (Roberts, 1989) is regarded as its junior synonym. Based on integrative taxonomy, three new species of Parambassis, previously misidentified as P. macrolepis, are newly described herein as Parambassis kapuasensis sp. nov., Parambassis seruyanensis sp. nov. and Parambassis sumatrana sp. nov., from West Kalimantan, Central Kalimantan and Sumatra, respectively. These species can be distinguished from each other by a series of morphological differences, including differences in head characteristics and the number of scales along the lateral line. A phylogenetic analysis based on the ‘barcode’ fragment of the mitochondrial cytochrome c subunit I (COI) gene showed that each species forms a monophyletic group, diverging to others by more than 3% uncorrected genetic distances. Furthermore, COI-based automatic species delimitation methods retrieved the same species-level taxonomic units, confirming the validity of all new species of Parambassis described in this work.